Evaluating immunologic response and clinical deterioration in treatment-naive patients initiating first-line therapies infected with HIV-1 CRF01-AE and subtype B - Rebecca A. Oyomopito (2018)
Background: HIV-1 group M viruses diverge 25%-35% in envelope, important for viral attachment during infection, and 10%-15% in the pol region, under selection pressure from common antiretrovirals. In Asia, subtypes B and CRF01-AE are common genotypes. Our objectives were to determine whether clinical, immunological, or virological treatment responses differed by genotype in treatmentnaive patients initiating first-line therapy. Methods: Prospectively collected longitudinal data from patients in Thailand, Hong Kong, Malaysia, Japan, Taiwan, and South Korea were provided for analysis. Covariates included demographics, hepatitis B and C coinfections, baseline CD4 T lymphocyte count, and plasma HIV-1 RNA levels. Clinical deterioration (a new diagnosis of Centers for Disease Control and Prevention category B/AIDS-defining illness or death) was assessed by proportional hazards models. Surrogate endpoints were 12-month change in CD4 cell count and virologic suppression post therapy, evaluated by linear and logistic regression, respectively. Results: Of 1105 patients, 1036 (93.8%) infected with CRF01-AE or subtype B were eligible for inclusion in clinical deterioration analyses and contributed 1546.7 person-years of follow-up (median: 413 days, interquartile range: 169-672 days). Patients > 40 years demonstrated smaller immunological increases (P = 0.002) and higher risk of clinical deterioration (hazard ratio = 2.17; P = 0.008). Patients with baseline CD4 cell counts > 200 cells per microliter had lower risk of clinical deterioration (hazard ratio = 0.373; P = 0.003). A total of 532 patients (48.1% of eligible) had CD4 counts available at baseline and 12 months post therapy for inclusion in immunolgic analyses. Patients infected with subtype B had larger increases in CD4 counts at 12 months (P = 0.024). A total of 530 patients (48.0% of eligible) were included in virological analyses with no differences in response found between genotypes. Conclusions: Results suggest that patients infected with CRF01-AE have reduced immunologic response to therapy at 12 months, compared with subtype B-infected counterparts. Clinical deterioration was associated with low baseline CD4 counts and older age. The lack of differences in virologic outcomes suggests that all patients have opportunities for virological suppression. Copyright © 2012 by Lippincott Williams and Wilkins.